IMPLEMENTASI KURIKULUM PEMBELAJARAN AL-QUR’AN DI MADRASAH IBTIDAIYAH DALOPO - Supriyono; Fitri Puji Rahmawati; Anik Gufron (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to evaluate the implementation of the curriculum in Al-Qur'an learning at MI Muhammadiyah Dolopo, develop a concept for optimizing the implementation of the curriculum in Al-Qur'an learning at MI Muhammadiyah Dolopo, describe the learning process and the academic achievements of students in Al-Qur'an learning at MI Muhammadiyah Dolopo. This study uses a qualitative naturalism methodology, including participant observation, in-depth interviews, and document tracing as data collection techniques. The three stages of activities consist of data analysis techniques using qualitative descriptive methods: reduction, data display, and conclusion drawing. The results of the study indicate that the implementation of the Al-Qur'an learning curriculum at MI Muhammadiyah Dolopo has been running well but still requires some improvements to achieve optimal results. One of the challenges faced is the lack of adequate resources and facilities. The study also found that support from parents and the surrounding community is very important for the success of the Al-Qur'an learning program. Optimization can be achieved through improving the quality of teachers and providing better learning facilities.